Profile of geographical variation in marginal land and its relationship with the fruit tree species richness in Jombang District, Indonesia: - - Zulfikar ZULFIKAR; ENDANG ARISOESILANINGSIH; SERAFINAH INDRIYANI; ADJI ACHMAD RINALDO FERNANDES4 (Society for Indonesian Biodiversity, 2021)
Abstract. Zulfikar, Arisoesilaningsih E, Indriyani S, Fernandes AAR. 2021. Profile of geographical variation in marginal land and its relationship with the fruit tree species richness in Jombang District, Indonesia. Biodiversitas 22: 3315-3325. The purpose of this study was to determine the sites of fruit tree species richness, in order to analyze the relationship between the locations with fruit tree diversity, and geographical variations, towards the success of marginal land conservation in Jombang Regency. The study area covered four districts, and was divided into 11 sites with different slopes and altitudes. Multivariate analysis was carried out using the R program. The results showed that the structure and composition of fruit trees were discovered to be 21 species from 14 families. The uniqueness of the fruit trees was shown in Tamarindus indica and Cocos nucifera, which were observed as rare plants on slopes with high and low altitudes, respectively. The results of the geographical variation analysis also showed that the slope and elevation with values of 0.5889 and 0.5077, respectively, were significantly correlated with the site of fruit plant species richness at the (?) 0.05 level, as the response formed was not linear for the three geographical diversities studied. Also, the model built between site, slope, and elevation towards the fruit tree species richness was acceptable, due to the fact that the value (Pr> F) = 0.004 was very significant at the (?) 0.001 level.